ANALISA DAN SIMULASI KREDIT MOTOR BERBASIS WEB - Indah Ariyati (LPPM STMIK ANTAR BANGSA, 2014)
Abstract— The development of the information system via the Internet is used as a means of improving information in almost all areas of business , both areas of commerce , industry and services . Making the web-based information systems as a means of promotion is effective and efficient and easily accessible to internet users . The authors designed a website on credit analysis motor poured in question-a question that often arises when the credit application the motor . The website can also be used to apply for credit motorcycle . For users who would apply for credit motorcycle loan can perform simulations as a benchmark or a provisional estimate for the data-data related to motor loans . The authors designed the analysis and simulation of motors credit by using the web -based programming language PHP and MySQL to perform credit simulations themselves and do their own credit analysis online.